Re: Ashley M. Hopkins, Ganessan Kichenadasse, Christos S. Karapetis, et al. Concomitant Proton Pump Inhibitor Use and Survival in Urothelial Carcinoma Treated with Atezolizumab. Clin Cancer Res. In press. https://doi.org/10.1158/1078-0432.CCR-20-1876 - Satoshi Funada; Takashi Yoshioka; Yan Luo (European Urology Oncology, 2020)
Purpose Advanced sarcomas lack effective maintenance therapies after first-line chemotherapy. We present long-term phase 1 results evaluating multi-antigen stimulated cell therapy-I (MASCT-I), a novel immunotherapy integrating dendritic cell vaccination with adoptive T-cell transfer, as maintenance treatment (NCT03034304). Patients and methods Thirty-one patients with disease control after chemotherapy received MASCT-I alone (n = 17) or with ifosfamide (n = 14). The primary endpoint was safety. Secondary endpoints included progression-free survival (PFS), overall survival (OS), time to progression (TTP), objective response rate (ORR), and disease control rate (DCR). Exploratory objective comprised evaluation of the relationship between clinical efficacy and antigen-specific immune responses. Results Treatment was well tolerated with no treatment-related deaths. After a median follow-up of 63.6 months, median PFS from maintenance initiation (PFS1) was 9.5 months, and from first-line chemotherapy start (PFS2) was 16.2 months; median OS was 33.8 months. The combination with ifosfamide numerically improved survival outcomes compared to monotherapy. Patients with high antigen-specific immunity were significantly positively associated with prolonged survival. Notably, six of the seven patients who maintained progression-free status for over 4 years exhibited robust immune activation. Conclusions Our findings establish MASCT-I alone or combined with chemotherapy as maintenance treatment that elicits sustained antigen-specific immunity and encouraging survival in advanced sarcoma.